Long-term Clinical Effectiveness of Ustekinumab in Patients with Crohn's Disease Who Failed Biologic Therapies: A National Cohort Study. (16th April 2019) - Liefferinckx, Claire; Verstockt, Bram; Gils, Ann; Noman, Maja; Van Kemseke, Catherine; Macken, Elisabeth; De Vos, Martine; Van Moerkercke, Wouter; Rahier, Jean-Francois; Bossuyt, Peter; Dutré, Joris; Humblet, Evelien; et al.
Abstract: Background: Ustekinumab [UST] was recently approved in Europe for the treatment of moderate to severe Crohn's disease [CD]. Long-term real-world data are currently scarce for CD patients previously exposed to several biologics. Methods: This is an observational, national, retrospective multicentre study. Patients received intravenous UST 6 mg/kg at baseline, with 90 mg subcutaneously thereafter every 8 weeks. Response and remission rates were assessed at Weeks 8, 16, and 52. Results: Data from 152 patients were analysed. All patients were exposed to at least one anti-TNFα agent, with 69.7% were exposed to even two anti-TNFα and vedolizumab. After 1 year, 42.1% and 25.7% of patients had experienced clinical response and clinical remission, respectively, and 38.8% and 24.3% had achieved steroid-free clinical response and remission, respectively; 38.8% of patients discontinued therapy during the 12 months of follow-up. Colonic location was predictive of clinical response at 1 year, and low body mass index [BMI] at baseline was a negative predictor of clinical remission. Resolution of arthralgia was associated with clinical response over time. De novo arthralgia was reported by 17.9% of patients at Week 8 and 13.5% of patients at Week 52. No impact of UST on arthralgia was observed in patients with concomitant ankylosing spondylitis [ n = 17]. Others adverse events were reported in 7.2% of patients. Conclusions: This real-world cohort study confirms the effectiveness of UST in CD patients previously exposed to several biologics. Ustekinumab was well tolerated with respect to adverse events. Podcast: This article has an associated podcast which can be accessed at https://academic.oup.com/ecco-jcc/pages/podcast